Rediscovery of the holotype of Trochilus maria Gosse, 1849 (Aves: Apodiformes: Trochilidae) - Graves, Gary R.; Prys-Jones, Robert P. (Zootaxa, 2011)
Trochilus maria Gosse, 1849, was described from a specimen obtained by Richard Hill from the “mountains of Manchester,” most likely the Don Figueroa Mountains in Manchester Parish, Jamaica (Rapkin, 1851). Gosse (1849a: 258) quoted field notes from Hill stating that the specimen “was startled from a nest in which were two young ones, and was obtained by charging some of the blossoms of the mountain-pride (Spathelia simplex) on which it was feeding, with minute doses of strychnine. As soon as it sucked from one of the poisoned chalices, it fluttered, and fell dead.” Gosse (1849a: 258) provided a detailed plumage description (see below) and summarized, “It is near to Polytmus, but differs from it in the inferior length of its beak, and in the colours of the plumage; but being apparently young, it is impossible to say what the adult condition may prove. I am happy however to fortify my own judgment by that of Mr. Gould, who on my showing it to him decidedly pronounced it new.”